1998
DOI: 10.1098/rspb.1998.0266
|View full text |Cite
|
Sign up to set email alerts
|

Improving vision: neural compensation for optical defocus

Abstract: Anecdotal reports abound of vision improving in myopia after a period of time without refractive correction. We explored whether this effect is due to an increased tolerance of blur or whether it reflects a genuine improvement in vision. Our results clearly demonstrated a marked improvement in the ability to detect and recognize letters following prolonged exposure to optical defocus. We ensured that ophthalmic change did not occur, and thus the phenomenon must be due to a neural compensation for the defocus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
159
1
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(173 citation statements)
references
References 23 publications
12
159
1
1
Order By: Relevance
“…The lens that was used to induce optical blurring has the same action as a low-pass spatial filter because it attenuates information that is carried at high spatial frequencies and results in degradation of the retinal image. 16 The reduction of the amount of visual cortex activity caused by dioptric defocus probably reflects this loss of visual information transferred from retina to visual cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lens that was used to induce optical blurring has the same action as a low-pass spatial filter because it attenuates information that is carried at high spatial frequencies and results in degradation of the retinal image. 16 The reduction of the amount of visual cortex activity caused by dioptric defocus probably reflects this loss of visual information transferred from retina to visual cortex.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that improvement in visual resolution after blur adaptation is ascribed to a compensatory process in visual cortex. For example, Mon-Williams et al 16 found visual acuity improvement after a 30-minute period of ϩ1D induced defocus caused by "neural compensation," which occurred at binocular sites in visual cortex. Georgeson and Sullivan 19 also stated that organization of spatial frequency selective channels in the visual cortex attempts to restore the clarity of the blurred image.…”
Section: Discussionmentioning
confidence: 99%
“…3). Subjective evaluation of image quality depends on previous blur experience and adaptation (Mon-Williams et al, 1998;Webster et al, 2002;Khan et al, 2013). It was suggested (Mon-Williams et al, 1988) neuronal recalibration occurred, which involved spatial frequency sensitivity changes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [1][2][3][4][5] have demonstrated that a certain period of exposure to the defocus blur (blur adaptation) improves visual acuity, suggesting the presence of a neural circuit that compensates for blur. More recently, Artal et al [6] suggested that the mechanism underlying blur compensation functions effectively for more complex blur caused by higher-order aberrations.…”
Section: Introductionmentioning
confidence: 98%